Uncommon Glomus Tumor at The Volar Area of Distal Phalang: a Case Report - WIDODO, WAHYU; TRIYUDANTO, ARYO NUGROHO (Indonesian Journal of Cancer, 2017)
ABSTRACTIntroduction: Glomus tumor, a benign rare neoplasmic perivascular lesion arising from glomus neuromial-arterial tissue. Glomus cells, which are found in the dermis throughout the body, are responsible for thermoregulation. In this tumor, its cells proliferate and surround the vascular canals, producing a classic clinical sign such as spontaneous pain, pain on light touching, and temperature hyperesthesia. Despite its rare occurrence, it is necessary to know how recognize and treat this variant of perionychium tumor. Case Illustration: A forty-seven-year old woman came with pain on the tip of her ring finger since 3 years before admission. Over time, the tingling sensation worsened and eventually pain emerged. The appearance of her ring finger and nail were normal. However, the patient felt pain after a light touch and paresthesia especially at the volar side of her ring finger. Having normal radiograph appearance, excisional biopsy was then performed. Histologic examination showed a well-defined lesion encapsulated by a fibrous capsule. The lesion consisted of several thin-walled flared vascular containments with layers of glomus cells around it, which is in accordance with characteristic of benign glomus tumor.At the latest follow up, there were no complication or recurrence found. The pain and paresthesia around the ring finger were also diminished. Conclusion: Despite its rare occurrence, the diagnosis of Glomus Tumor can be performed clinically. Excisional biopsy is the definitive treatment and specific diagnostic modality for Glomus Tumor.ABSTRAKGlomus tumor adalah tumor jaringan lunak yang cukup jarang ditemui dan merupakan lesi perivaskular yang muncul dari arteri glomus neuromial. Sel glomus berproliferasi dan mengelilingi kanal vaskular. Tumor ini sering ditemukan pada area subungual. Tanda khasnya adalah nyeri spontan, nyeri pada sentuhan ringan, dan sensitivitas terhadap suhu. Kemampuan mengenali dan mengobati tumor perionychium ini penting. Wanita usia 47 tahun datang dengan keluhan utama nyeri pada jari manis sejak 3 tahun lalu. Seiring waktu, sensasi kesemutan dan nyeri memburuk. Pada pemeriksaan fisik di regio distal phalang tidak ditemukan bengkak dan kemerahan, deformitas, atau massa. Kulit intak tanpa perubahan warna dengan sekitar. Kuku tampak normal. Pada palpasi didapatkan nyeri pada sentuhan ringan di area volar dengan VAS 4-5 dan paresthesia pada sisi volar. Pemeriksaan x-ray menunjukkan hasil normal. Pada pemeriksaan biopsi eksisional dan pemeriksaan histopatologi ditemukan lesi berbatas tegas yang terdiri atas kapsula fibrosa dengan beberapa lapis dinding dan vaskular serta sel glomus yang menutupinya. Tiga bulan pasca-operasi tidak ditemukan nyeri dan paresthesia pada lokasi tumor. Tumor glomus adalah tumor yang jarang dan dapat didiagnosis melalui tampilan klinis. Biopsi eksisional merupakan pengobatan definit, sekaligus modalitas diagnostik spesifik.